PENGARUH SISTEM PELAPORAN AKUNTANSI DAN TINGKAT KEPATUHAN PAJAK TERHADAP KUALITAS PELAYANAN BISNIS UMKM DI DESA SUMBERMULYO - Fahmadya, Elok Kunzita; Mahmud, M. Bahrudin; Febrianti, Yulia; Susilo, Dwi Ermayanti (Media Mahardhika, 2024)
This study aims to analyze the impact of accounting reporting systems and tax compliance on the quality of business services within Micro, Small, and Medium Enterprises (MSMEs) in Sumbermulyo Village, Jombang. MSMEs play a significant role in Indonesia's economy, contributing to job creation and societal welfare. However, they face challenges in areas such as accounting reporting and tax compliance, both of which are critical to enhancing business service quality. A reliable accounting system helps mitigate financial mismanagement, while a high level of tax compliance prevents penalties and fosters consumer trust. The research employs a quantitative descriptive approach, using data collected from questionnaires distributed among tofu production companies in Sumbermulyo. Data analysis techniques include normality tests, multicollinearity, and F-tests, which are used to examine the relationships between the variables and draw conclusions regarding their influence on service quality.